(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Jadidism movement is an important cultural and political movement formed in Central Asia in the late 19th and early 20th centuries. In this article, we will try to analyze in depth the heritage of the Jadids, studying their contribution to the national revival and cultural changes. In the framework of the article, we will reflect on the main principles of the Jadidism movement, its history, founders, and their influence on the fields of education, culture and politics.